Analyzing the risks of fixed deposit investments and real estate and their impact on enhancing the credit rating of insurance companies: An applied study in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research seeks to know the size of the risks to which investments in fixed deposits and real estate are exposed, and the extent of their impact on the credit rating of the national insurance company. Here, a recent topic appears in the Iraqi insurance market, which is the credit rating of insurance companies.  Covering the theoretical side of the research, As for the practical side, the data and information contained in the records of the National Insurance Company (the research sample) for the period from 2009-2020 were approved, as well as personal interviews through field visits. The statistical method was also adopted. One of the most important conclusions is that the National Insurance Company and insurance companies in Iraq do not have A credit rating, whether a credit rating from local or international agencies, and one of the most important recommendations that came out of the research is the attempt to establish an institution specialized in credit rating for insurance companies in Iraq, characterized by its ability to absorb the specificity and nature of the local market, From experts and specialists in the field of credit evaluation of the insurance sector to carry out the evaluation process as a nucleus of the credit rating model in cooperation with the Central Bank of Iraq, the Ministry of Finance, and the Insurance Bureau, and the cost is less than the cost of international credit rating agencies.